1993
DOI: 10.1111/j.1476-5381.1993.tb13752.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of NG‐nitro‐l‐arginine methyl ester on the cardiovascular system of the anaesthetized rabbit and on the cardiovascular response to thyrotropin‐releasing hormone

Abstract: 1 The effects of 300 mg kg-' of the nitric oxide (NO) inhibitor NG-nitro-L-arginine methyl ester (L-NAME) on the regional blood flow, on the flow response to 1 mg kg-' of thyrotropin-releasing hormone (TRH) and on cerebral blood flow autoregulation were studied in urethane anaesthetized rabbits subjected to unilateral sectioning of the cervical sympathetic chain. The blood flow measurements were performed by the tracer microspheres method. 2 The cerebral arteriovenous difference in oxygen saturation (CAVOD) wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
1
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 32 publications
3
30
1
1
Order By: Relevance
“…However, it may be noted that under pentobarbitone anaesthesia, capillary blood flow is approximately one-third of the total carotid blood flow (Saxena & Verdouw, 1982;1985;Den Boer et al, 1992;present results) and thus the basal release of NO may already be too low to detect a significant decrease. In contrast to a number of studies which reported a moderate reduction in cerebral blood flow following NOsynthase inhibition, suggesting a basal NO-release in this part of the cranial circulation (Kovaich et al, 1992;Prado et al, 1992;Seligsohn & Bill, 1993), in our present experiments L-NAME failed to reduce the cerebral component of carotid blood flow. The absence of an endothelial NO-dependent dilator tone is supported by the recent finding that cultured rat brain microvessel endothelial cells do not show basal release of NO (Durieu-Trautmann et al, 1993).…”
Section: Regional Carotid Bloodflowcontrasting
confidence: 55%
See 1 more Smart Citation
“…However, it may be noted that under pentobarbitone anaesthesia, capillary blood flow is approximately one-third of the total carotid blood flow (Saxena & Verdouw, 1982;1985;Den Boer et al, 1992;present results) and thus the basal release of NO may already be too low to detect a significant decrease. In contrast to a number of studies which reported a moderate reduction in cerebral blood flow following NOsynthase inhibition, suggesting a basal NO-release in this part of the cranial circulation (Kovaich et al, 1992;Prado et al, 1992;Seligsohn & Bill, 1993), in our present experiments L-NAME failed to reduce the cerebral component of carotid blood flow. The absence of an endothelial NO-dependent dilator tone is supported by the recent finding that cultured rat brain microvessel endothelial cells do not show basal release of NO (Durieu-Trautmann et al, 1993).…”
Section: Regional Carotid Bloodflowcontrasting
confidence: 55%
“…Gardiner et al, 1990;Van Gelderen et al, 1991). In doses up to 30 mg kg-', both L-NAME and N0-nitro-Larginine (L-NOARG) are without effect on brain blood flow (Van Gelderen et al, 1991;Faraci & Heistad, 1992), though in higher doses these agents can significantly reduce cerebral blood flow (Kovach et al, 1992;Prado et al, 1992;Seligsohn & Bill, 1993). It is tempting to speculate that at high doses NO-synthase inhibitors may act at a different site within the brain.…”
Section: Regional Carotid Bloodflowmentioning
confidence: 97%
“…There is now compelling evidence to support the view that endothelium-derived nitric oxide is an important mediator of vasomotor tone in the eye (for review see Koss, 1999). For example, inhibition of nitric oxide synthase in vivo in a wide range of species reduces basal ocular blood¯ow, as measured using radiolabelled microspheres (Nilsson, 1996;Hardy et al, 1996;Seligsohn & Anders, 2000) or laser Doppler¯owmetry (Zagvazdin et al, 1996;Koss, 1998;Luksch et al, 2000). It remains to be determined whether this tonic vasodilator in¯uence of nitric oxide on the ocular vasculature in vivo is derived from the endothelium as a result of basal release or release stimulated by agonists (Benedito et al, 1991a;Gidday & Zhu, 1995) or by¯ow (Rubanyi et al, 1986), or is derived from perivascular nitrergic nerves (Nilsson, 1996;Toda et al, 1998;Zagvazdin et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In rabbits, a high dose of L-NAME has been shown to induce a marked reduction in blood flow in the retinal blood vessels (Seligsohn et al 1993). These blood vessels are restricted to the myelinated fiber layer of the retina and can therefore be regarded as an extension of the optic nerve into the eye.…”
Section: Role Of No In the Optic Nervementioning
confidence: 99%
“…The observation that inhibitors of NO formation cause intraocular vasoconstriction following either intravenous (Granstam et al 1993;Mann et al 1995;Seligsohn & Bill 1993;Vogel et al 1994) or local (Donati et al 1994;Meyer et al 1993) administration indicates that, in fact, N O is normally released in the eye. As in many other tissues, NO release from the endothelial cells of the blood vessels is expected (Bergua 1995;Chakravarthy et al 1995).…”
mentioning
confidence: 99%